Study of association between management styles of head nurses with nurses’ empowerment in Medical and Surgical Wards in Hospitals of NEZAJA Health and Medical Services in Tehran 1388 - Sefidpoush, parvin; pazargadi, mehrnoosh; khazaei, nahid; Alavi Majd, hamid (Advances in Nursing & Midwifery, 2012)
Abstract Background and Aim: Managers by adopting effective management styles can improve efficiency and quality of care and empowerment of personnel .The aim of present research is to examine the correlation between management styles of head nurses with nurses’ empowerment in medical and surgical wards in hospitals of NEZAJA Health and Medical Services in Tehran 1388. Material and Method: This research is a descriptive correlational study.A sample of 57 sataff nurses, 26 head nurses and 5 senior managers participated in the study.A questionnaire which consisted of three sections was used for gatherind data. These sections includeds :1 (Nurse clinical competence scale for assessing nurses’ empowerment 2) Psychological empowerment questionnaire to study nurses’ Psychological empowerment 3) questionnaire of Leader Effectiveness and Adaptability description to study head nurses management styles. Content validity andface validity were used for assuring the validity of questionnaires.Reliability of tools was obtained by test re-test. Data were analyzed by SPSS14 software. Findings: Finding of the research showed that most head nurses(65/4%) reported that they use selling management style . The empowerment level of nurses from the three view points (nurses , head nurses , their managers) were reported at good level ( 50- 70) and at very good level ( 3/1 - 4 ) for nurses’ Psychological empowerment .There was no significant association between head nurses’ management style with empowerment of nurses. Conclusion Appropriate changes in organizational structure andrelationships are necessary for achieving a dynamic system in organizations. Key words :management styles,empowerment,nurse , Medical and Surgical Wards